Degradation of acetaminophen by electro-fenton and photoelectro-fenton processes using a cylindrical-type electrochemical cell - Cada, Crisanto A. Jr. (2012)
aPersistent Organic Pollutants (POPs) from human and veterinary Pharmaceutical and Personal Care Products (PPCPs) are continuously introduced to the aquatic environment. In this study, Acetaminophen (ACT) is the target pollutant. ACT is a widely used over-the-counter drug and is one of the most commonly detected drugs in bodies of water. The effects of initial pH, Fe2+ loading, and H2O2 concentration by Electro-Fenton (EF) and Photoelectro-Fenton (PEF) processes were assessed to determine the highest ACT percentage removal. Result of parametric studies showed pH 3 as the ideal pH level of the solution. At pH 3, increasing the FE2+ loading and H2O2 concentration to maximum (from 0.01 to 0.10 mM and 5 to 25 mM), improved the degradation efficiency of ACT. The ACT percent removal attained for both EF and PEF processes showed that FE2+ and H2O2 positively affect the degradation efficiency of ACT, while pH was the reverse. The optimum conditions obtained using Design Expert 7 software for acetaminophen degradation were at pH 3, 0.01 mM Fe2+, and 10.72 mM H2O2 for he EF process and at pH 3, 0.02 mM Fe2+, and 7.24 mM H2O2 for the PEF process. The ACT removal efficiency for EF process was 89% while 90% ACT removal was observed for PEF process operated at optimum conditions. Reliability of the BBD model was proven by determining the difference between the predicted and actual results of EF and PEF processes. For COD, the percent removal was 33 and 37 for EF and PEF processes, respectively.
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman
Keywords: Acetaminophen; Sewage -- Purification -- Biological treatment; Electro-Fenton process; Fenton process